Applying Swedish programmes projecting forest development to Polish forestry conditions : a study made on data from Gostynin forest district in Poland - Skreta, Magdalena (SLU/Southern Swedish Forest Research Centre, 2006)
The paper deals with problems of applying Swedish programmes projecting forest development to Polish forestry conditions. The study was made on data from the Lucien forest sub-district in the Gostynin forest district (Regional Board of State Forests-National Forest Holding in Lodz). The data was applied to three programmes: Forest Time Machine, ProdMod and SFanalys with the matrix model. The aim of the work is to test the potential for some Swedish forestry computer programmes' application to the data from other country. This was realized by comparing the volume output from computer programmes Forest Time Machine and ProdMod with the figures from Polish growth and yield tables, describing required modifications of input to the programmes and discussing the influence of data modifications on the output from the programmes, as well as on the possibilities of the programmes' application in Poland. The volume estimations from ProdMod and Forest Time Machine were dissimilar to the data from Polish growth and yield tables. Further studies are needed to evaluate the reliability of the programmes' predictions. The thesis presents some recommendations for possible changes in the programmes' structure to make them more useful in Polish conditions.